Analisis Pengaruh LDR, NIM & BOPO terhadap NPL Yang Terdaftar Di BEI Priode 2021 sampai 2023 - Fiqih, Muhammad; Ardiansyah, Ardiansyah (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to present empirical evidence on the effect of Loan to Deposit Ratio, Net Interest Margin, and operational efficiency as measured by operational expenses and income on the level of Non-Performing Loans in the banking sector. The method used in this study is multiple linear regression. The research population includes all banking companies listed on the Indonesia Stock Exchange from 2021 to 2023. This research sample was obtained through purposive sampling technique, with a total of 32 Corporations that met the criteria, resulting in 96 observations that were analyzed using statistical software. Data analysis was carried out using the Random Effect Model (REM) approach in E-Views 12 software. The results of the study show that the LDR and NIM variables do not have a significant impact on NPL, while the BOPO variable is proven to have a significant effect on NPL.